Czasopisma lokalne gminy Wierzchosławice w latach 1990-2009 - Gleisner, Iwona (Acta Universitatis Lodziensis. Folia Librorum, 2010)
The subject of this article is a development of local press in Wierzchoslawice borough between 1990 and 2009 on the basis of four the most significant periodicals, two of which are published to this day. Apart from presenting theoretical issues about a local press in Poland, the author describes Wierzchoslawice borough and the first attempts at publishing press there. In the further part of the article more important titles were discussed that are published locally since 1992. The young press of Wierzchoslawice looks quite good against local press in Poland. Till this day there are two periodicals published regularly: “Ziemia Wierzchoslawicka”, published by the Cultural Centre of Wierzchoslawice Borough, and “Piast z Zagrody Wincentego Witosa” a periodical closely connected with people’s movement, strongly developed in the homeland of a man who was the Prime Minister three times, and is published by the Friends of Wincenty Witos Museum Society. For many citizens of this borough they are the main source of information regarding their surroundings. In this article you can also find “Gminne Zwierciadlo”, the only private periodical published between 1994 – 2001, as well as “Biuletyn Informacyjny” published by the Society of Cultivation the Knowledge of the Home Army. The latter has been on the market a short time but its specific content is interesting enough to have a stable place in the history of the local press of Wierzchoslawice.